Hepatic echinococcosis (E.H.): analysis of 92 cases - Porras, Yamandú; Méndez Aserito, Hugo (Cirugía del Uruguay, 1973)
Statistics · presented by the Surgery Service of the Mercedes Hospital comprise 92 cases of Hepatic echinococcosis over a 10-year period. Clinical features, comp!ications, morbility causes and death-rate are anaIyzed and conclusions regarding therapy employed are consigned.